Characterization of the sialic acid-binding site in sialoadhesin by site-directed mutagenesis. - Vinson, M; van der Merwe, P; Kelm, S; May, A; Jones, E; Crocker, P (1996)
The sialoadhesins are a distinct subgroup of the immunoglobulin superfamily, comprising sialoadhesin, CD22, the myelin-associated glycoprotein, and CD33. They can all mediate sialic acid-dependent binding to cells with distinct specificities. Sialoadhesin is a murine macrophage-restricted cell-surface molecule with 17 extracellular immunoglobulin-like domains that recognizes NeuAc alpha 2-3Gal in N- and O-glycans and interacts preferentially with cells of the granulocytic lineage. Its sialic acid-binding site is located within the NH2-terminal (membrane-distal) V-set domain. Here we have carried out site-directed mutagenesis in an attempt to identify the binding site of sialoadhesin. A subset of nonconservative mutations disrupted sialic acid-dependent binding without affecting binding of three monoclonal antibodies directed to two distinct epitopes of sialoadhesin. A CD8 alpha-based molecular model predicts that these residues form a contiguous binding site on the GFCC'C" beta-sheet of the V-set domain centered around an arginine in the F strand. A conservative mutation of this arginine to lysine also abolished binding. This amino acid is conserved among all members of the sialoadhesin family and is therefore likely to be a key residue in mediating sialic acid-dependent binding of sialoadhesins to cells.